Assessment of services provided by Tiquatira Linear Park, Sao Paulo, SP (Brazil) - Biagolini, Carlos Humberto; Lourenço, Roberto Wagner (Revista Hipótese, 2016)
The Linear Park Tiquatira was the first linear park in the city of São Paulo and receives hundreds of people every day seeking onsite space for recreation; sporting activities; socializing or physical exercise on the equipment installed in the park. Like all public parks, the Linear Park Tiquatira provides services to the population, so this study aimed to evaluate the quality of services provided. Interviews were conducted with 95 users of the park, as well as assigning values to important park items. After evaluation with the methodology developed for this purpose, the Linear Park Tiquatira reached 85.6 points; considered an excellent Linear Park. The evaluation of public spaces becomes important in order to compare with other similar spaces and allow improvements in those with lower levels, allowing to public spaces provide quality service regardless of neighborhood or where is inserted the Linear Park assessed.